MENCERMATI ASPEK PENGARUSUTAMAAN GENDER DALAM PENEMPATAN PEGAWAI PADA POSISI STRUKTURAL DALAM BIROKRASI DI PROVINSI SULAWESI SELATAN - Ariana, Ariana; Sukri, Sukri; Ekawaty, Dian (JPP (Jurnal Politik Profetik), 2018)
This study aims to examine and analyze determinants factors of implementation of gender mainstreaming in the appointment of structural officials policy in the South Sulawesi Province governmental bureaucracy structures. Through the qualitative research research and case study approach, the research was conducted in the Provincial Government institution on Education Affairs. As the result, the appointment of structural officials position show that there are two factors that determine the gender mainstreaming policies in the structural appointment process. Those are the internal factors and external factors. The Internal factors that had influence implementation of gender mainstreaming policies based this research findings are the resources, implementing organizations, communication, coordination and implementing commitment, and support of bureaucratic structures factors.  On the other hand, the external factors are includes: social political influence, cultural influences and bureaucratic characteristics, and policy design support.